The effects of weight gain after smoking cessation on atherogenic α1-antitrypsin–low-density lipoprotein - Komiyama, Maki (Heart Vessels, 2014)
Although cardiovascular risks decrease after quitting smoking, body weight often increases in the early period after smoking cessation. We have previously reported that the serum level of the α1-antitrypsin–low-density lipoprotein complex (AT–LDL)—an oxidatively modified low-density lipoprotein that accelerates atherosclerosis—is high in current smokers, and that the level rapidly decreases after smoking cessation. However, the effects of weight gain after smoking cessation on this cardiovascular marker are unknown. In 183 outpatients (134 males, 49 females) who had successfully quit smoking, serum AT–LDL levels were measured using an enzyme-linked immunosorbent assay. For all persons who had successfully quit smoking, body mass index (BMI) significantly increased 12 weeks after the first examination (p < 0.01). Among patients with a BMI increase smaller than the median, a significant decrease (p < 0.01) in serum AT–LDL values was found, but no significant changes in serum AT–LDL values were found in patients with a BMI increase greater than the median. The findings suggest that the decrease in serum AT–LDL levels after quitting smoking is influenced by weight gain after smoking cessation.